Pengaruh Variasi Kecepatan Udara Terhadap Kinerja Tungku Gasifikasi Sekam PAdi Tipe Downdraft Kontinu - Saputra, Nurhadi (2016)
Combustion is very rapid oxidation process between the fuel and oxidizer to cause ignition and heat. Based on the residual gas produced by burning differentiated into combustion and incomplete combustion, is an example of incomplete combustion in the gasification process. Gasification is a process of change thermochemical solid fuel into gas, where the necessary air is lower than the air used for combustion processes. The purpose of this study was to determine the effect of the speed of the combustion air to the combustion temperature, time and time startup effective flame furnace fueled gasification of rice husk continuous downdraft type. The study was conducted by varying the speed of air enters the furnace with a variable rate of 6.0 m / s, 7.0 m / s and 8.0 m / s, and then retrieve the data include combustion temperatures, ignition timing early and effective burning time. The results show the air speed variations affect the combustion temperature, time of the initial ignition and burning time effectively produced. At the air velocity of 6.0 m / s the highest temperature at the time of ignition 500.47oC 9.5 minutes and time effective flame for 35 minutes. Air velocity of 7.0 m / s the highest temperature at the time of ignition 559.51oC 7 minutes and time effective flame for 32 minutes. While on the air velocity of 8.0 m / s the highest temperature generated at the time of ignition 595.32oC 5.5 minutes and time effective flame for 28 minutes. Keywords: Air Speed, Gasification, Rice Husk, Temperature Combustion